Emprendimiento, factores que influyen en su constitución y sostenibilidad en la ciudad de Machala. - Chisaguano Macancela, Ana Gabriela (My University, 2021)
Currently, entrepreneurship is considered a factor of great importance for the economic growth of countries due to its role in reducing unemployment, inequality and poverty. Objective: To determine the factors that influence the constitution and sustainability of enterprises in the city of Machala. Method: The methods used in the research are descriptive, qualitative and explanatory, from where it is sought to determine those factors that affect the constitution and sustainability of enterprises. Results: The results show that there are several factors associated with the constitution and sustainability of enterprises, such as business vision, the motivations of the entrepreneur, the organizational factor, access to credit, among others. Conclusion: In order for the enterprises of the city of Machala to grow and remain in the market, it is necessary that aspects such as: new technologies, learning of administrative, financial, economic and accounting issues be considered.
En la actualidad el emprendimiento es considerado un factor de gran importancia para el crecimiento económico de los países debido a su rol en la disminución del desempleo, desigualdad y pobreza. Objetivo: Determinar los factores que influyen en la constitución y sostenibilidad de los emprendimientos en la ciudad de Machala. Método: Los métodos empleados en la investigación son el descriptivo, cualitativo y explicativo, desde donde se busca determinar aquellos factores que inciden en la constitución y sostenibilidad de los emprendimientos. Resultados: Los resultados demuestran que existen varios factores asociados con la constitución y sostenibilidad de los emprendimientos, como la visión empresarial, las motivaciones del emprendedor, el factor organizacional, el acceso al crédito, entre otros. Conclusión: Para que los emprendimientos de la ciudad de Machala puedan crecer y permanecer en el mercado es necesario que sean considerados aspectos como: nuevas tecnologías, aprendizaje de temas administrativos, financieros, económicos y contables.
Keywords: EMPRENDIMIENTO; CONSTITUCIÓN; SOSTENIBILIDAD; CRECIMIENTO ECONÓMICO